Modified Lagrangian Methods for Separable Optimization Problems - Abdelouahed Hamdi; Aiman A. Mukheimer (Abstract and Applied Analysis)
We propose a convergence analysis of a new decomposition method to solve structured optimization problems. The proposed scheme is based on a class of modified Lagrangians combined with the allocation of resources decomposition algorithm. Under mild assumptions, we show that the method generates convergent primal-dual sequences.